IDEOLOGY, TECHNOLOGY, AND TRANSLATION IMPACT - Ibroximova Malokhatbonu,; Karimova Gulsanam,; Solomboyeva Oʻgʻiloy,; Shamsutdinova Nazokat, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article explores the complex relationship between ideology, technology, and their combined impact on the field of translation. It investigates how ideological frameworks influence translation choices and practices, while technological advancements shape the methods and tools available to translators. By analyzing the interplay between these factors, the study highlights the evolving nature of translation in the digital age and its socio-political implications. The article argues that understanding this dynamic is essential for both translators and scholars to navigate the challenges and opportunities of contemporary translation.